Toxicological Effects of Silver Nanoparticles (Ag-NPs) on Different Physiological Parameters of Tadpoles, Polypedates maculatus - Pattanayak, R.; Das, Rakesh; Das, A.; Padhi, S. K.; Sahu, S. S.; Pattnaik, S.; Mishra, C. S. K.; Mishra, S. S.; Mohanty, C. S.; Sinam, G.; Barman, H. K.; Sundaray, J. K.; et al. (International Journal of Bio-resource and Stress Management, 2018)
The effects of silver nanoparticles (Ag-NPs) on the growth, metamorphosis, innate immune parameters and enzyme profiles of tadpole, Polypedates maculatus were studied. Chronic exposure to Ag-NPs for 60 days at 1 mg l-1 and 5 mg l-1 concentrations caused 10% and 50% mortalities respectively alongwith slow growth and delayed metamorphosis as compared to 0.1 mg l-1 treatment and control (0 mg l-1). The non-specific immune parameters and certain enzyme activities like alkaline phosphatase (ALP), superoxide dismutase (SOD) and lactate dehydrogenase (LDH) varied significantly in a dose dependent manner. The accumulation of silver in the tadpole tissues of treated groups ranged from 0.0966±0.0025 µg g-1 to 0.4718±0.0126 µg g-1 as compared to tissues in control group (0.0758±0.0019 µg g-1). Hence Ag-NPs had significant detrimental effects on growth and other associated physiological parameters of tadpole, Polypedates maculatus when administered at higher concentrations (>1 mg l-1) for longer durations. Thus the toxicity studies of Ag-NPs have to be conducted on wider ranges of target and non-target species to assess their environmental impacts. Furthermore, these results suggest that silver nanoparticles induce a dose-dependent toxicity in physiological parameters of tadpoles, which hinders normal development.This study was aimed to enhance our insight on the health and environmental impact of silver nanoparticles. This study pointed out the adverse effects of Ag-NPs in tadpole species and all applications involving silver nanoparticles should be given special attention and promoted only after detailed studies.